Linear and non-linear optimization models for the selection of investment portfolio - Vakrinienė, Sigutė; Misevičius, Gintautas (Lietuvos matematikos rinkinys, 2021)
This research suggests a maxmin model for the selection of investment portfolios. The risk evaluation coefficients are introduced. The components of portfolio are found by solving linear programming task in onemodel and non-linear programming task in the other.  In the experimental part of the research ineffective portfolios exerted from these models are tested referring to the statistical data of the Baltic stock market. Realizations of the suggested portfolios with different risk coefficient values are compared to realizations of effective (Pareto optimal) portfolios.
Keywords: investment portfolio; linear programming; non-linear programming; matrix game